O grotesco e a personagem feminina em contos de Flannery O'Connor - Barcala, Débora Ballielo [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
O presente trabalho pretende analisar os contos “A Stroke of Good Fortune”, “A Temple of the Holy Ghost”, “Good Country People”, “A View of the Woods”, “Revelation” e “Parker’s Back”, da escritora estadunidense Flannery O’Connor considerando o que neles há de grotesco. Será dada especial atenção à representação do corpo grotesco, isto é, o corpo deformado, amputado, modificado, doente. Uma vez considerados os elementos grotescos, serão realizadas análises das personagens femininas nos contos: como elas são construídas e o que isso pode representar em termos de subversão da autoridade patriarcal e das particularidades da escrita de Flannery O’Connor. Por fim, serão feitas aproximações entre o grotesco e a representação da mulher nos textos da autora. Para a realização desta pesquisa, tomaremos por base as obras dos teóricos sobre o grotesco Wolfgang Kayser (2013), Mikhail Bakhtin (2013) e Mary Russo (2000); além de estudos sobre a escrita de Flannery O’Connor como a obra de Katherine Prown (2001) e outros teóricos que abordam análise de personagens.

The present work intends to analyse the short stories "A Stroke of Good Fortune", "A Temple of the Holy Ghost", "Good Country People", "A View of the Woods", "Revelation" and "Parker's Back", by the American writer Flannery O'Connor, considering what is grotesque in them. Special attention is going to be paid to the representation of the grotesque body - the deformed, amputee, modified, sick body. Once the grotesque elements are considered, analyses of the female character is going to be carried out: how they are constructed and what it may represent in terms of subversion of the patriarchal authority and of the particularities of Flannery O'Connor's writing. Finally, approximation between the grotesque and the representation of the woman is going to be done based on the author's stories. This research is going to be based on the works of the grotesque theorist Wolfgang Kayser (2013), Mikhail Bakhtin (2013) and Marry Russo (2000), besides studies about Flannery O'Connor's writing such as the work of Katherine Prown (2001) and other theorists of character analysis.
The grotesque and the female character in short stories by Flannery O'Connor
Keywords: Flannery O’Connor; Grotesco; Literatura de autoria feminina; Personagem feminina; Grotesque; Female authorship; Female character